Foveal avascular zone and vessel density in healthy subjects: An optical coherence tomography angiography study - Falavarjani, Khalil; Shenazandi, Hamideh; Naseri, Dariush; Anvari, Pasha; Kazemi, Pegah; Aghamohammadi, Farzaneh; Alissmail, Feras; Alemzadeh, Sayyed (Journal of ophthalmic & vision research, 2018)
Purpose: To report the normal characteristics and correlations of the foveal microvascular networks using optical coherence tomography angiography (OCTA) in a healthy Iranian population. Methods: Enface 3x3 OCTA images were obtained using the RTVue Avanti spectral-domain optical coherence tomography with AngioVue software (Optovue, Fremont, CA, USA). Foveal avascular zone (FAZ) area, central foveal point thickness and inner retinal thickness at the foveal center and the vascular density of the superficial retinal capillary plexus (SCP) and deep retinal capillary plexus (DCP) in the fovea were recorded. Results: Seventy normal eyes of 70 subjects (range, 9 to 71 years) were studied. Mean FAZ area was 0.32 ± 0.11 (range, 0.13-0.67) mm2 in SCP and 0.50 ± 0.13 (range, 0.19-0.94) mm2 in DCP. Mean SCP vessel density was 29.6 ± 4.7 (range, 16.3-40.3) % in the fovea. Mean DCP vessel density was 27.0 ± 5.9 (range, 15.0-45.2) % in the fovea. The FAZ area at SCP level was negatively correlated to the central subfield thickness (P < 0.001). The FAZ area at DCP level correlated negatively to the central subfield thickness and was significantly associated to age (both P < 0.001). The foveal SCP vessel density significantly correlated with foveal thickness and the foveal DCP vessel density correlated significantly with central foveal subfield thickness and was inversely related to age (all P < 0.05). Conclusion: In this study, central foveal subfield thickness was a major determinant of the FAZ size and foveal vessel density. Age was a determinant for FAZ area and whole image vessel density in DCP.